A Critical Analysis of the Grade 3 English Textbook in Bangladesh: Strengths and Weaknesses - Md. Kabir Hossain (Universitas Pahlawan Tuanku Tambusai, 2026)
An English textbook plays a crucial role in learning English as a foreign language (EFL) in Bangladesh. This is a qualitative content analysis study whose aim is to investigate the strengths and weaknesses of the grade 3 English textbook in Bangladesh. The textbook is a key instructional material that is analysed in six separate dimensions of strengths and weaknesses based on the theories proposed by Hutchinson, Waters, Cunningsworth, and McGrath. Many investigations have been carried out concerning the teaching and learning of the English language at the primary level. However, existing literature has not sufficiently explored whether the shortcomings stem from the textbooks themselves. Thus, this study is significant in such a context as it aims to address the gap in this area in the literature through a critical analysis of the nature and quality of the textbooks. The findings show that the English textbook contains some strengths, such as communicative teaching strategies, integration of reading, writing, speaking, and listening skills, active learning activities, attractive design and visual appeal, real-life contents, and integration of moral and social values. Similarly, the weaknesses are vocabulary-related issues, insufficient grammatical explanation, a shortage of writing practice, a lack of pronunciation guides, insufficient critical thinking activities, and traditional evaluation systems. It concludes that the implications of this article’s findings help to achieve the general objectives of the national curriculum and Sustainable Development Goal 4.